The role of social media in enhancing the learning process of Iraq students - Alaa Ibrahim Mahmood Al-Nuaimi, ALI; Asmael Hamed, Wathq; Hadi Ali, Ahmed (International Journal of Engineering and Technology, 2019)
Social media platforms are used to facilitate social interaction, likewise, the social media enhances and complements the traditional schoolroom teaching. This study examines the role of social media in enhancing the learning process by exploring the impact of student perceptions of social media, Engagement and Interaction with peers in enhancing the learning process among female students. The use of social media platform was noticed to be great among female students. Female students would opt to use improved learning methods by changing their learning styles to connect with an environment that has more dynamic social potentials, rather than studying in isolated environments that offers traditional learning styles. The positive impact of social media on the enhancement of learning processes comprises the learning style, relationship between students and experience of social media use, by nurturing social interaction and the sharing of knowledge particularly among female students in order to expedite social interaction, because female students are more comfortable with sharing ideas among their peers. This study employs the quantitative survey method among female students, and the results indicated that, the use of social media improves the learning process among Iraqi secondary schoolgirls through student perceptions, Engagement and Interaction with peers.Â Â Â